Agriculture and water resources: UNFCCC influence on Peruvian adaptation regulations to increase resilience against climate change - Arana-Ruedas, Del Piero R. (2022)
Agriculture and water resource are highly threatened due to climate change, increasing the probability of backsliding on almost every aspect of sustainable development worldwide. For instance, water resource distribution throughout the Peruvian territory is not homogeneous. Hydrometeorological phenomena also threaten it, so it is crucial for the agriculture sector and water management to increase resilience against climate change. The study aims to understand the Peruvian conduct under the United Nations Framework Convention on Climate Change (UNFCCC) regime. Its influence in the Peruvian adaptation regulation and public institutions over the years and the interaction with the latest commitment to the UNFCCC related to climate change agriculture - water resources. The methodology used for the study was qualitative, delivered throughout a documentary analysis, and narrative design among scientific papers, UNFCCC documentation, and Peruvian regulation to weave the experience occurred and the sequences of the events to set up a general narrative. The results show that Peru has active participation in the UNFCCC, particularly under a neoliberalism approach. The convention pushed institutional and regulatory development of the Peruvian Government constantly. Also, after the Paris Agreement, one of the most important influences was the implementation of Law N° 30754 on climate change, which articulates all the regulations related to it, providing a national, more substantial legally-binding commitment. Finally, it is important for Peru to analyze the achievement of current adaptation actions and keep studying the impacts of climate change at a local level to develop a bottom-up approach for an effective policy formulation-implementation.